A Review of the Effectiveness of Product-Based Approach in the Teaching of Writing - Burhansyah Burhansyah; Masrizal Masrizal (Proceedings of AICS - Social Sciences, 2021)
In the teaching of writing, there are generally several ways proposed by scholars, two of which commonly practised by teaching practitioners are the teaching of writing as product and process. The product-based approach, despite being a traditional way of teaching writing, still exists in the field of writing pedagogy. This is because many ELT practitioners seem to prefer this approach to any other. This paper therefore intends to look at this approach in terms of its features and effectiveness. The research used the method of library research; it was conducted by searching for relevant literature from different types of sources such as books, journals, and research reports. Based on the findings of the library study, it was found that, despite having some drawbacks, the product-based approach has several noticeable advantages. First, this approach can assist students to know how to produce a piece of writing with correct grammar. The other advantage is that the product-based approach seems suitable for students who are preparing for examinations and English proficiency tests such as the IELTS and TOEFL tests, the focus of which is usually on the end product. These advantages, among some others, appear to make this approach still have a place in the field of writing pedagogy.